2005
DOI: 10.1007/s11243-005-3147-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of mononuclear cadmium(II) and dinuclear uranyl(VI) complexes with vic-dioximes

Abstract: In this study, the mononuclear complexes of cadmium(II) and dinuclear complexes of uranyl(VI) with five vicdioximes have been obtained. Cadmium(II) forms, with ligands, complexes [(L x H)(Cl)(H 2 O)(Cd)] with x ¼ 1-5. Mononuclear complexes with a metal:ligand ratio of 1:1 were obtained for cadmium(II) with the ligands, and a chloride ion and a water molecule are also coordinated to the cadmium(II) ions. Uranyl(VI) complexes of these ligands are a dinuclear structure with l-hydroxo-bridges. Uranyl(VI) forms, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 31 publications
0
22
0
1
Order By: Relevance
“…Elde edilen bu bileşiklerin termal davranışları (TGA-DTG) incelendiğinde literatürdeki benzer bileşiklerle yaklaşık değerler gösterdiği ve termal kararlı maddeler sınıfında yer alacağı görülmüştür (Saleh et al, 2003;Canpolat et al, 2005 Kurtoğlu et al, 2008 (Selwood, 1956). …”
Section: Ligandlarınunclassified
“…Elde edilen bu bileşiklerin termal davranışları (TGA-DTG) incelendiğinde literatürdeki benzer bileşiklerle yaklaşık değerler gösterdiği ve termal kararlı maddeler sınıfında yer alacağı görülmüştür (Saleh et al, 2003;Canpolat et al, 2005 Kurtoğlu et al, 2008 (Selwood, 1956). …”
Section: Ligandlarınunclassified
“…chemical shifts for the ligand, nickel(II), zinc(II), cadmium(II) and uranyl(VI) complexes is given in chemical shift in the 10.22 p.p.m. range as a singlet, which indicates an (E,E)-structure for the dioxime [11,26]. In the 1 H-n.m.r.…”
Section: Ir Spectramentioning
confidence: 97%
“…Vic-dioximes and their coordination compounds are widely used for various purposes in analytical, pigment, biological chemistry, chemical industry, medicinal chemistry and model compounds [2][3][4][5]. In our previous studies we investigated the synthesis and characterization of various transition metal complexes of new vic-dioximes [6][7][8][9][10][11][12][13][14][15][16]. In the present paper we report the synthesis and characterization of mononuclear Co II , Ni II , Cu II , Zn II , Cd II and dinuclear UO 2 VI complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that ligands from oximes, semicarbazones, and thiosemicarbazones may be able to be used as chelators (Babahan et al 2006;Ibrahim et al 2000;Lee et al 2003). The potential to use the ligands as chelators in phytoremediation is supported by their proven ability as biologically active metal chelates for essential applications such as reducing vitamin B12 (Babahan et al 2006;Canpolat et al 2005;Para 2004). In fact, semicarbazones have been shown to form complexes with Cd, Co, Cu, Fe, Mn, Ni, Pb, and Zn (Nigam et al 2000;Para and KarolczykKostuch 2002).…”
Section: Introductionmentioning
confidence: 99%